2007
DOI: 10.4049/jimmunol.179.12.8305
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Fever Temperature Induces a Protective Stress Response in T Lymphocytes Mediated by Heat Shock Factor-1 (HSF1)

Abstract: Heat shock factor-1 (HSF1) is a transcription factor that serves as the major temperature-inducible sensor for eukaryotic cells. In most cell types, HSF1 becomes activated to the DNA binding form at 42°C and mediates the classical heat shock response, protecting the cells from subsequent lethal temperatures. We have recently demonstrated that HSF1 is activated at a lower temperature in T lymphocytes than in most other cell types (39°C vs 42°C), within the physiological range of fever. In this study, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 57 publications
5
42
0
1
Order By: Relevance
“…Partial activation of HSF1 has been described during exposure to febrile, sub-heat shock temperatures [28], [29], [30], [31]. To investigate whether COX-2 expression may be induced at febrile temperatures in endothelial cells, HUVECs were either kept at 37°C or were incubated at 40 and 41°C for 8 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Partial activation of HSF1 has been described during exposure to febrile, sub-heat shock temperatures [28], [29], [30], [31]. To investigate whether COX-2 expression may be induced at febrile temperatures in endothelial cells, HUVECs were either kept at 37°C or were incubated at 40 and 41°C for 8 hours.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 ؉ T cell activation is not impaired in HSF1-deficient mice. We previously showed that HSF1-deficient T cells incubated at an elevated temperature (39.5°C) had an impaired ability to proliferate in response to anti-CD3/CD28 stimulation in vitro compared with T cells isolated from HSF1 ϩ/ϩ mice (26). Given these results, we predicted that L. monocytogenesinfected HSF1-deficient mice might have a decreased CD8 ϩ T cell response because of the fever induced during the first few days of infection.…”
Section: Monocytogenes Infection Triggers An Increase In Core Bodymentioning
confidence: 89%
“…We previously showed that the transcription factor HSF1 was important for protecting T cell function when T cells were incubated at elevated temperatures within the range of a physiological fever response (26). To address the role of HSF1 during bacterial infection, we chose to study L. monocytogenes, since clearance of this intracellular bacterial pathogen is known to be strictly dependent on T cells (6,19).…”
Section: Monocytogenes Infection Triggers An Increase In Core Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Fever-range whole body thermal therapy has been shown to enhance the host immune response, whereas extreme systemic thermal therapy (41.5– 42°C) may impair immune function [14,15]. Fever-range hyperthermia can induce expression of heat shock proteins [16, 17], enhance antigen presentation by dendritic cells [18, 15], promote dendritic cell maturation [18, 14] and activate immune effector cells (T lymphocytes and NK cells) [15, 19, 20]. New studies suggest that fever-like temperatures also activate an innate immune response by promoting toll-like receptor 4 (TLR4) signaling [21].…”
Section: Introductionmentioning
confidence: 99%